Dynamics of Industrial Electricity Demand in the State of Bahia (Brazil): Evolution of Price and Income and COVID-19 Implications - Martins, Luís Oscar Silva; Fernandes, Fábio Matos; Santos, Alex A. B.; Bittencourt, Euclides Santos; Silva, Marcelo Santana (International Journal of Energy Economics and Policy, 2023)
The growth in demand for electricity is a determining factor for the regional development. This research aimed to estimate the price and income elasticity parameters of the industrial demand for electricity in the State of Bahia, Brazil, from January 2003 to June 2022, in addition to making forecasts for the period from July to December 2022. After verifying that some of the analyzed data were non-stationary, we chose to use the cointegration method, estimating the econometric model through the Error Correction Mechanism (ECM). The ECM considers the model’s variables and their lags, relating the series’ short and long-run trends. The estimated parameters were inelastic and presented the following values: 0.501 and 0.762 (price and income, long-run) and 0.482 and 0.702 (price and income, short-run). The adjustment coefficient between the short and long-run was also statistically significant and indicated that approximately 8% of the difference between the effective value and the long-run value (balance value) is corrected in each period, demonstrating the rigidity of the consumption structure of electricity in the industrial sector in Bahia. The model also demonstrated an 8.1% reduction in consumption during COVID-19 incidence period. Regarding the forecasts, they proved to be robust and with an average difference of 5.4% in relation to what actually happened in the months of July and August 2022. Thus, the calculated parameters are configured as another source of information for public policymakers and private investors interested in the electricity sector in the State of Bahia.